Validity of a new sport-specific endurance test in artistic gymnastics - Mkaouer, B.; Amara, S.; Bouguezzi, S.; Abderrahmen, A. B.; Chaabene, H. (Frontiers in Sports and Active Living, 2023)
Introduction: General and particularly sport-specific testing is an integral aspect of performance optimization in artistic gymnastics. In artistic gymnastics, however, only non-specific field tests have been used to assess endurance performance (e.g., Multistage Shuttle Run Test; Cooper's Test).